The economic significance of increasing population income - Esankulov Ulug’bek (THE INNOVATION ECONOMY, 2026)
The article reveals the inextricable link between income growth and economic growth. In particular, it high lights how increases in wages, pensions, and social benefits affect consumer demand. It also discusses approaches to increasing incomes through employment policy and supporting entrepreneurship